2021
DOI: 10.1002/stc.2891
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous identification of densely instrumented structures using line topology sensor networks

Abstract: Summary In this paper, a new strategy for vibration‐based structural health monitoring is proposed, specifically designed for smart sensors with edge computing capabilities organized in a line topology. This solution is aimed at maximizing resource optimization and enables the identification of modal parameters even for large or densely instrumented structures, where star‐topology monitoring systems are typically unsuitable. In particular, an efficient data management procedure is proposed to reduce data trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This strategy was proposed in previous studies (Quqa et al., 2022; Quqa et al, 2023) and will be used here to represent the reference performance of a DNN‐based method to solve the inverse ERT problem. This DNN will be referred to as “preliminary” DNN hereafter, as it is trained on synthetic data alone.…”
Section: Deep Learning For Distributed Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy was proposed in previous studies (Quqa et al., 2022; Quqa et al, 2023) and will be used here to represent the reference performance of a DNN‐based method to solve the inverse ERT problem. This DNN will be referred to as “preliminary” DNN hereafter, as it is trained on synthetic data alone.…”
Section: Deep Learning For Distributed Sensingmentioning
confidence: 99%
“…Previous studies showed that, in some cases, synthetic data alone could be enough to train neural networks for the identification of conductivity changes due to damage or strain variations when the sensing body is originally undamaged (Quqa et al., 2022). Nevertheless, while early damage might be identified with good accuracy (Quqa et al, 2023), the performance of neural networks typically degrades with damage severity (L. Chen, Gallet, et al., 2022; Hallaji et al., 2014; Seppänen et al., 2017). However, not all surface disconnections are necessarily related to structural damage.…”
Section: Introductionmentioning
confidence: 99%
“…For example, WSS can easily be implemented to build sensor networks that meet the requirements of sudden event monitoring with minimal power consumption [ 9 ]. They can be exploited to handle system identification for densely instrumented infrastructures and structures [ 10 ]. They offer versatile networks that can be interfaced with a variety of sensors (accelerometers, strain gauges, thermistors, LIDAR, etc.)…”
Section: Introductionmentioning
confidence: 99%